Spatiotemporal variability of meteorological droughts and pasture resilience in Somalia using SPEI and resilience metrics - Jaabir Hussein; Eskinder Gidey; Franco Bilotto; Dmaris Mbui; Jason Sircely (Discover Sustainability)
Abstract Somalia's arid and semi-arid climate makes it highly vulnerable to drought, posing serious challenges to water resource management and agricultural productivity. This study investigates pasture resilience and the spatiotemporal variability of meteorological drought in northwestern Somalia, focusing on spring and autumn rainy seasons. The Standardized Precipitation Evapotranspiration Index (SPEI) was used to assess drought frequency, severity, and intensity from 1981 to 2020, while the sequential Mann–Kendall test detected significant temporal shifts. A resilience matrix was applied to quantify drought resistance and recovery capacity in pasturelands. Our analysis shows a significant increase in drought severity over the last four decades, with extreme and severe droughts occurring more frequently, particularly in the spring season. The decade from 2001 to 2010 recorded the highest occurrence of extreme droughts. Eastern Somaliland experienced more frequent and intense droughts than western areas, with a sharp decline in annual SPEI (− 1.08) and a notable shift in 2002. Although moderate droughts were common, it is the rise in extreme droughts that poses the greatest risk to livelihoods and ecosystems. These findings underscore the urgent need for region-specific drought mitigation strategies, especially during the primary growing seasons in eastern Somaliland.